Acoustic emissions and pressure stimulated currents experimental techniques used to verify Kaiser effect during compression tests of Dionysos marble (Fracture and Structural Integrity, 2017)
The damage development due to externally applied mechanical stress is a hot topic of interest involving several applications of everyday life, like civil engineering, monument restoration, construction evaluation and health monitoring. Repetitive loadings of brittle materials cause internal damages that gradually extend, leading to inevitable failures. Such processes are studied under the concept of the materials’ mechanical memory effect that is widely known as Kaiser effect. The Kaiser effect states that a structure will only suffer further internal damaging when exposed to applied stresses higher than previously encountered. Certain conditions lead to a violation of the Kaiser effect, known as the Felicity effect, quantitatively measured using the Felicity Ratio. This work presents the experimental results when repetitive mechanical load loops are applied on marble specimens, while concurrent Acoustic Emission (AE) and Pressure Stimulated Currents (PSC) measurements are conducted. The collected AE and PSC data are studied in combination with the mechanical data, like mechanical stress and strain, under the frame of the Kaiser effect. It is clearly seen that the Felicity ratio strongly depends on the stress range the material is subjected to, with regard to the elastic or plastic deformation region.
Keywords: Acoustic Emissions; Pressure Stimulated Currents; Dionysos marble; Kaiser effect; Felicity Ratio